Implementasi Artificial Intelligence Terhadap Perkembangan Digital Kewarganegaraan Mahasiswa - Susi; Yayuk Muji Rahayu; Nur Amalia Zahra; Siti Mariyatul Koimah (Academy of Education Journal, 2025)
This study analyzes the impact of artificial intelligence (AI) implementation on the development of digital citizenship among university students. By leveraging AI, the learning process becomes more personalized, interactive, and inclusive, enhancing digital literacy and understanding of digital ethics, privacy, and data security. The methodology used is a literature review, collecting data from various scientific articles and journals. Findings show that AI increases student engagement and learning outcomes through instant feedback and adaptive material adjustments. Challenges such as technological dependence, which may weaken critical thinking, and limited access to technology and digital literacy were identified. Therefore, a holistic approach is needed, considering ethical aspects, infrastructure, and digital literacy. This study provides recommendations for educators and policymakers on effective AI implementation strategies.